Green Bioplastics as Part of a Circular Bioeconomy. (March 2019) - Karan, Hakan; Funk, Christiane; Grabert, Martin; Oey, Melanie; Hankamer, Ben
Abstract : The rapid accumulation of plastic waste is driving international demand for renewable plastics with superior qualities (e.g., full biodegradability to CO2 without harmful byproducts), as part of an expanding circular bioeconomy. Higher plants, microalgae, and cyanobacteria can drive solar-driven processes for the production of feedstocks that can be used to produce a wide variety of biodegradable plastics, as well as bioplastic-based infrastructure that can act as a long-term carbon sink. The plastic types produced, their chemical synthesis, scaled-up biorefinery concepts (e.g., plant-based methane-to-bioplastic production and co-product streams), bioplastic properties, and uses are summarized, together with the current regulatory framework and the key barriers and opportunities. Highlights: Fossil fuel and plastic production are currently integrated. About 80% of manufactured plastic accumulates as waste in landfills and natural environments, presenting an increasing hazard. Biodegradable and bio-based plastics present a viable and attractive alternative. Well-crafted legislated standards on plastic biodegradability and environmental and animal/human health impacts could fast-track and optimize industry transition. The diversity of bio-based feedstocks opens up the opportunity to produce an expanding range of renewable plastics. Biodegradable plastics should ideally fully degrade to CO2 and water without harmful byproducts. Durable bioplastics can act as carbon sinks if well integrated into large-scale long-term infrastructure. Biorefinery and GMO strategies can support viable business development and the emerging circular bioeconomy.